Robotic Parathyroidectomy: A Prospective Case Control Study. - Arora,A; Garas,G; Awad,Z; Budge,J; Cox,J; Palazzo,F; Tolley,NS (Otolaryngol Head Neck Surg, 2012)
Objective: 1) To assess the clinical efficacy and cost-effectiveness of the robotic approach compared with conventional targeted minimally invasive parathyroidectomy. 2) To evaluate whether the absence of a neck scar associated with the robotic approach offers any advantage(s) over conventional targeted minimally invasive parathyroidectomy. 3) To compare patient satisfaction between the 2 techniques. Method: Prospective case control study of 30 patients that underwent targeted parathyroidectomy over 4 years (May 2009-February 2012) in a tertiary referral endocrine center. Fifteen patients had a robotic and 15 an endoscopic approach. Outcomes assessed included operative time, blood loss, biochemistry, pain, scar cosmesis, voice, quality of life, and complications. Results: In all cases the parathyroid adenoma was successfully removed. There was 1 robotic conversion. Mean robotic operative time was approximately double that of the conventional approach. There were no significant differences in mean blood loss. Initial normalization of PTH and adjusted serum calcium levels occurred in 29 cases. The mean visual analogue score (VAS) for scar cosmesis was superior in the robotic cohort from 2 weeks (84% vs 65%, P < .01) to 1 year (94% vs 62%, P < .01). Postoperative VAS pain scores were similar in both groups (P < .05). All EQ5 HD quality of life parameters significantly improved in both cohorts (P < .05). Conclusion: The robotic approach is a feasible "scar-less in the neck" alternative to conventional targeted minimally invasive parathyroidectomy with a superior cosmetic outcome. However, this novel approach is not suitable for all patients and appropriate patient selection is vital. Finally, the high cost of robotic parathyroidectomy currently hinders its more widespread use.